Interior problem in a nonsymmetric theory of gravitation - S. Ragusa (Brazilian Journal of Physics, 2006)
The field equations of a previous metric nonsymmetric theory of gravitation are considered for the interior ofa static spherically symmetric perfect fluid with a view to a study of stellar equilibrium. The equations are putinto a form of four first-order differential equations which are ready for numerical integration.